Parent Education is Changing: A Review of Smartphone Apps. Issue 5 (September 2017) - Davis, Deborah Winders; Logsdon, M. Cynthia; Vogt, Krista; Rushton, Jeff; Myers, John; Lauf, Adrian; Hogan, Felicia
Abstract: Purpose: The purpose was to critique existing parenting apps using established criteria and health literacy guidelines. Study Design: Descriptive methodology was used. Methods: The Apple App Store was searched using the terms parenting, child health, and infant health. To be included, the apps had to have relevant content (parenting, child health, or infant health), be in English, and contain parent education. After eliminating apps that failed to meet inclusion criteria from the original 203 apps, 46 apps were reviewed. The Patient Education Materials Assessment Tool was used to evaluate the health literacy subscales called Understandability and Actionability. Content analysis included Authority, Objectivity, Accuracy, Timeliness, and Usability. Results: The majority of the apps (70%) were in English only. The price ranged from free to $4.99. The purpose, target audience, and topics varied. Although all included apps were for parents, some were for more targeted groups of parents. The source of the information was not presented in 26% of the apps. Most apps took the user to a Web site or an article to read. Functionality of the apps was limited, with none of them providing a customized experience. Clinical Implications: Much development and research is needed before mobile health (mHealth) solutions can be recommended by nurses caring for new parents. It is critical that consumers and interdisciplinary professionals be involved in the early design phase of the product to ensure that the end product is acceptable and usable and that it will lead to healthy behaviors. Abstract : A critique of 46 parenting apps available in a commonly used online app store is presented using established criteria and health literacy guidelines. Many of the apps do not offer details of the source of their information and there was limited functionality, with none providing a customized experience. Mobile health solutions require rigorous research before nurses can recommend them as valid and reliable avenues for parent education.